An Appraisal of Husband’s Support for Contraceptive Use in Low Resource Setting of Chattogram City, Bangladesh - Khan, A. K. M. Ziaur Rahman; Zakaria, Muhammad (Asia Social Issues, 2021)
This study aimed to explore the current status concerning the roles of husbands in family planning and to identify the associated factors in the slum areas of Chattogram city in Bangladesh. A community-based cross-sectional study was conducted among the women living in different slums (N = 400) of Chattogram city. Data were collected using a structured and facilitator-administered questionnaire. Cross tabulation with chi-square tests and multivariate logistic regression analyses were performed using IBM SPSS version 24.0. This study revealed that 70.5% of the husbands supported wives’ contraceptive use. This study explored that husbands’ having education (OR = 2.45, 95% CI: 1.42-4.22), having two children (OR = 0.37, 95% CI: 0.18-0.76) and more than two children (OR = 0.21, 95% CI: 0.09-0.50), more utility facility in the slum areas (OR = 2.32, 95% CI: 1.15-4.68), a good relationship between husband and wife (OR = 1.97, 95% CI: 1.13-3.44), commencing reproductive health communication after the birth of the second child (OR = 0.43, 95% CI: 0.19-0.99), respondents’ having moderate knowledge on RH (OR =4.46, 95% CI: 2.10-9.46) and husbands’ visiting any health center to take wives’ reproductive health care (OR = 2.08, 95% CI: 1.06-4.09) were the predictors for supporting their wives in terms of contraceptive use.